2019
DOI: 10.4194/1303-2712-v19_12_01
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study the effect of black cumin seed (Nigella sativa) on nonspecific defense mechanisms of rainbow trout (Oncorhynchus mykiss) was investigated. The percentage of black cumin seed in diet were 0.0; 0.5; 1.0; 2.5; 5.0; 10.0 and 20.0 g/kg respectively. Rainbow trout (O. mykiss) of initial weights 108.7±17g were used for experiment. The biometric measurements and the blood parameters were determined in each group after feeding 7, 15, 25, 40 and 60 days respectively. In 7 day experiment, plasma protein, MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, at the end of the experimental period the overall mean averages of body weight for the groups were 142. Elmonem et al (2002) found that dietary addition of black seed (Nigella sativa) at levels 0, 3, 6 and 9 % displayed positive effects on growth performance.…”
Section: -Growth Performance Body Weight (Bw) and Body Weight Gain (Bwg)mentioning
confidence: 99%
“…Moreover, at the end of the experimental period the overall mean averages of body weight for the groups were 142. Elmonem et al (2002) found that dietary addition of black seed (Nigella sativa) at levels 0, 3, 6 and 9 % displayed positive effects on growth performance.…”
Section: -Growth Performance Body Weight (Bw) and Body Weight Gain (Bwg)mentioning
confidence: 99%